Metodologiczne podstawy badania zawartooeci prasy lokalnej - Kowalczyk, Ryszard (Przegląd Politologiczny, 2018)
The paper contains the author’s considerations on the methodological foundations for the examination of the content of local press. In discussing the content of local press, the author places it in the grid of linguistic as well as politological, sociological and psychological paradigms. He presents the structure of local press content and its criteria, the form of press materials, their topics, division into press genres, the attitude of press materials to reality, and its assessment and evaluation. The paper is concluded with considerations into the territorial aspects of press materials.